Java / An Introduction to Computer Science & Programming - Savitch, Walter J. (Prentice Hall, 2001)
A concise, accessible introduction to Java. Introduction to Computers and Java Objects, Primitive Types and Strings and Interactive I/ O, Flow of Control, Defining Classes and Methods, More About Objects and Methods, Arrays, Inheritance, Exception Handling, Streams and File I/ O, Dynamic Data Structure, Recursion, Window Interfaces Using Swing Objects, Applets and HTML, More Swing Objects, Graphic Objects, Index.